The effect of 5-aminolevulinic-acid (ALA) on the development of Saintpaulia ionantha - Tilly Mándy, A.; Honfi, P.; Stefanovits-Bányai, É.; Mosonyi, I. D.; Köbli, V.; Hrotkó, K. (International Journal of Horticultural Science, 2010)
In recent work the effect of 5-aminolevulinic-acid (ALA) agent (commercial name Pentakeep-V) was examined on the chlorophyll content, growth and development of Saintpaulia ionantha. The newly re-rooted potted plants were irrigated or sprayed with 0.3‰ or 0.5‰ Pentakeep-V solution, and plus 30% long lasting fertilizer was added to half of the all treatments. Control plants were sprayed with tap water. Best result were obtained on the field of flowering. All the treatments promoted chlorophyll-content in the leaves especially spraying with 0.3‰concentration. Plants treated with Pentakeep-V in both concentrations and independently from the spraying or irrigation flowered more than two weeks earlier than control and those that got plus 30% fertilizer. Besides in the case of some treatments the diameter of leaf rosette, the number and surface size of leaves grew comparing to the control. The longlasting fertilizer had positive effect on the fresh weight but none of treatments had effect on the dry weight.